АУЫР МЕТАЛЛ ТҰЗДАРЫНЫҢ ҚЫЗЫЛ ИЕК ҰЛПАЛАРЫНЫҢ ҚҰРЫЛЫМЫНА ƏСЕРІ (Experimental biology, 2009)
An experiment on rats showed that an action of chlorid cadmium caused changes in structure of gum mucous membrane, such as enlargement of intercellular space, increase of epithelium covering penetration and decrease of volume density of lesmosomal contacts. Thus, a prolonged action of chlorid cadmium on gum mucous membrane caused sufficientchanges in its structure and it didn`t completely restore even in the nearest time after intoxication stopping.
Keywords: membrane; chlorid cadmium